Conserving Biological Diversity in the Small Islands: Introducing the Center for the Conservation of Maluku’s Biodiversity - Leunufna, Semuel; Ralahalu, Karel A.; Anema, Liewe S. (European Journal of Applied Sciences, 2022)
Maluku province (islands), Indonesia belongs to an area of world’s biodiversity hot-spot, wallacea hot-spot, in which conservation efforts should be concentrated due to high endemic biodiversity components present and habitat destructions the area is undergoing. Center for the conservation of Maluku’s biodiversity (CCMB) is therefore established with the aim of assisting the government in policy making and activities related to the conservation and sustainable use of biological diversity. Following its initiation in the year 2006, the main activities of the CCMB has been directed to building and improving the knowledge and awareness of the importance of biodiversity and its continuing presence for the benefit of Maluku community now and in the future. Development of conservation institutions implementing various conservation systems, methodologies and techniques including inter-situ conservation through community gene-banks or on-farm management conserving cultural and semi-wild crop plants, ex-situ conservation through government funded gene-banks, as well as in-situ conservation are the plans for further activities of the CCMB.